Martin Escardo, started 5th May 2018
\begin{code}
{-# OPTIONS --safe --without-K --exact-split #-}
module Naturals.Order where
open import MLTT.Spartan
open import Naturals.Addition renaming (_+_ to _+'_)
open import Naturals.AbsoluteDifference
open import Naturals.Properties
open import Notation.Order
open import Ordinals.Notions
open import UF.DiscreteAndSeparated
open import UF.Subsingletons
_≤ℕ_ : ℕ → ℕ → 𝓤₀ ̇
zero ≤ℕ n = 𝟙
succ m ≤ℕ zero = 𝟘
succ m ≤ℕ succ n = m ≤ℕ n
instance
Order-ℕ-ℕ : Order ℕ ℕ
_≤_ {{Order-ℕ-ℕ}} = _≤ℕ_
≤-is-prop-valued : (m n : ℕ) → is-prop (m ≤ n)
≤-is-prop-valued zero n = 𝟙-is-prop
≤-is-prop-valued (succ m) zero = 𝟘-is-prop
≤-is-prop-valued (succ m) (succ n) = ≤-is-prop-valued m n
open import UF.Base
right-addition-is-embedding : (m n : ℕ) → is-prop (Σ k ꞉ ℕ , k +' m = n)
right-addition-is-embedding zero n (n , refl) (n , refl) = refl
right-addition-is-embedding (succ m) zero (k , p) (k' , p') =
𝟘-elim (positive-not-zero (k +' m) p)
right-addition-is-embedding (succ m) (succ n) (k , p) (k' , p') =
to-Σ-= (ap pr₁ IH , ℕ-is-set _ _)
where
IH : k , succ-lc p = k' , succ-lc p'
IH = right-addition-is-embedding m n (k , succ-lc p) (k' , succ-lc p')
subtraction : (m n : ℕ) → m ≤ n → Σ k ꞉ ℕ , k +' m = n
subtraction zero n l = n , refl
subtraction (succ m) zero l = 𝟘-elim l
subtraction (succ m) (succ n) l = pr₁ IH , ap succ (pr₂ IH)
where
IH : Σ k ꞉ ℕ , k +' m = n
IH = subtraction m n l
cosubtraction : (m n : ℕ) → (Σ k ꞉ ℕ , k +' m = n) → m ≤ n
cosubtraction zero n (.n , refl) = ⋆
cosubtraction (succ m) zero (k , p) = positive-not-zero (k +' m) p
cosubtraction (succ m) (succ .(k +' m)) (k , refl) =
cosubtraction m (k +' m) (k , refl)
zero-least : (n : ℕ) → zero ≤ n
zero-least n = ⋆
zero-least' : (n : ℕ) → ¬ (succ n ≤ zero)
zero-least' n l = l
zero-least'' : (n : ℕ) → n ≤ zero → n = zero
zero-least'' zero l = refl
succ-monotone : (m n : ℕ) → m ≤ n → succ m ≤ succ n
succ-monotone m n l = l
succ-order-injective : (m n : ℕ) → succ m ≤ succ n → m ≤ n
succ-order-injective m n l = l
\end{code}
We need the following modification of the first line of the following
function for this file to pass with the --double-check flag in Agda 2.6.3:
≤-induction : (P : (m n : ℕ) (l : m ≤ℕ n) → 𝓤 ̇ )
Reported as issue #6815
https://github.com/agda/agda/issues/6815
\begin{code}
≤-induction : (P : (m n : ℕ) (l : m ≤ n) → 𝓤 ̇ )
→ ((n : ℕ) → P zero n (zero-least n))
→ ((m n : ℕ) (l : m ≤ n)
→ P m n l
→ P (succ m) (succ n) (succ-monotone m n l))
→ (m n : ℕ) (l : m ≤ n) → P m n l
≤-induction P b f zero n ⋆ = b n
≤-induction P b f (succ m) zero l = 𝟘-elim l
≤-induction P b f (succ m) (succ n) l = f m n l (≤-induction P b f m n l)
succ≤= : (m n : ℕ) → (succ m ≤ succ n) = (m ≤ n)
succ≤= m n = refl
≤-refl : (n : ℕ) → n ≤ n
≤-refl zero = ⋆
≤-refl (succ n) = ≤-refl n
≤-trans : (l m n : ℕ) → l ≤ m → m ≤ n → l ≤ n
≤-trans zero m n p q = ⋆
≤-trans (succ l) zero n p q = 𝟘-elim p
≤-trans (succ l) (succ m) zero p q = 𝟘-elim q
≤-trans (succ l) (succ m) (succ n) p q = ≤-trans l m n p q
≤-anti : (m n : ℕ) → m ≤ n → n ≤ m → m = n
≤-anti zero zero p q = refl
≤-anti zero (succ n) p q = 𝟘-elim q
≤-anti (succ m) zero p q = 𝟘-elim p
≤-anti (succ m) (succ n) p q = ap succ (≤-anti m n p q)
≤-succ : (n : ℕ) → n ≤ succ n
≤-succ zero = ⋆
≤-succ (succ n) = ≤-succ n
unique-least : (n : ℕ) → n ≤ zero → n = zero
unique-least zero l = refl
unique-least (succ n) l = 𝟘-elim l
≤-split : (m n : ℕ) → m ≤ succ n → (m ≤ n) + (m = succ n)
≤-split zero n l = inl l
≤-split (succ m) zero l = inr (ap succ (unique-least m l))
≤-split (succ m) (succ n) l = cases inl (inr ∘ (ap succ)) (≤-split m n l)
≤-join : (m n : ℕ) → (m ≤ n) + (m = succ n) → m ≤ succ n
≤-join m n (inl l) = ≤-trans m n (succ n) l (≤-succ n)
≤-join .(succ n) n (inr refl) = ≤-refl n
≤-down : (m n : ℕ) → m ≤ succ n → (m ≠ succ n) → (m ≤ n)
≤-down m n l u = cases id (λ p → 𝟘-elim (u p)) (≤-split m n l)
≤-+ : (m n : ℕ) → (m ≤ m +' n)
≤-+ m zero = ≤-refl m
≤-+ m (succ n) = ≤-join m (m +' n) (inl IH)
where
IH : m ≤ m +' n
IH = ≤-+ m n
≤-+' : (m n : ℕ) → (n ≤ m +' n)
≤-+' m n = transport (λ k → n ≤ k) γ (≤-+ n m)
where
γ : n +' m = m +' n
γ = addition-commutativity n m
_<ℕ_ : ℕ → ℕ → 𝓤₀ ̇
m <ℕ n = succ m ≤ℕ n
instance
Strict-Order-ℕ-ℕ : Strict-Order ℕ ℕ
_<_ {{Strict-Order-ℕ-ℕ}} = _<ℕ_
<-succ : (n : ℕ) → n < succ n
<-succ = ≤-refl
not-less-than-itself : (n : ℕ) → ¬ (n < n)
not-less-than-itself zero l = l
not-less-than-itself (succ n) l = not-less-than-itself n l
not-less-bigger-or-equal : (m n : ℕ) → ¬ (n < m) → n ≥ m
not-less-bigger-or-equal zero n u = zero-least n
not-less-bigger-or-equal (succ m) zero = ¬¬-intro (zero-least m)
not-less-bigger-or-equal (succ m) (succ n) = not-less-bigger-or-equal m n
bigger-or-equal-not-less : (m n : ℕ) → n ≥ m → ¬ (n < m)
bigger-or-equal-not-less m n l u = not-less-than-itself n γ
where
γ : succ n ≤ℕ n
γ = ≤-trans (succ n) m n u l
less-not-bigger-or-equal : (m n : ℕ) → m < n → ¬ (n ≤ m)
less-not-bigger-or-equal m n l u = bigger-or-equal-not-less n m u l
bounded-∀-next : (A : ℕ → 𝓤 ̇ ) (k : ℕ)
→ A k
→ ((n : ℕ) → n < k → A n)
→ (n : ℕ) → n < succ k → A n
bounded-∀-next A k a φ n l = cases f g s
where
s : (n < k) + (succ n = succ k)
s = ≤-split (succ n) k l
f : n < k → A n
f = φ n
g : succ n = succ k → A n
g p = transport⁻¹ A (succ-lc p) a
\end{code}
Added 20th June 2018:
\begin{code}
<-is-prop-valued : (m n : ℕ) → is-prop (m < n)
<-is-prop-valued m n = ≤-is-prop-valued (succ m) n
<-coarser-than-≤ : (m n : ℕ) → m < n → m ≤ n
<-coarser-than-≤ m n = ≤-trans m (succ m) n (≤-succ m)
<-trans : (l m n : ℕ) → l < m → m < n → l < n
<-trans l m n u v = ≤-trans (succ l) m n u (<-coarser-than-≤ m n v)
<-split : (m n : ℕ) → m < succ n → (m < n) + (m = n)
<-split m zero l = inr (unique-least m l)
<-split m (succ n) l = ≤-split m n l
regress : (P : ℕ → 𝓤 ̇ )
→ ((n : ℕ) → P (succ n) → P n)
→ (n m : ℕ) → m ≤ n → P n → P m
regress P ρ zero m l p = transport⁻¹ P (unique-least m l) p
regress P ρ (succ n) m l p = cases (λ (l' : m ≤ n) → IH m l' (ρ n p))
(λ (r : m = succ n) → transport⁻¹ P r p)
(≤-split m n l)
where
IH : (m : ℕ) → m ≤ n → P n → P m
IH = regress P ρ n
<-is-well-founded : (m : ℕ) → is-accessible _<_ m
<-is-well-founded zero = acc (λ y l → unique-from-𝟘 l)
<-is-well-founded (succ m) = acc (τ (<-is-well-founded m))
where
τ : is-accessible _<_ m → (n : ℕ) → n < succ m → is-accessible _<_ n
τ a n u = cases (λ (v : n < m) → prev _<_ a n v)
(λ (p : n = m) → transport⁻¹ (is-accessible _<_) p a)
(<-split n m u)
course-of-values-induction : (P : ℕ → 𝓤 ̇ )
→ ((n : ℕ) → ((m : ℕ) → m < n → P m) → P n)
→ (n : ℕ) → P n
course-of-values-induction = transfinite-induction _<_ <-is-well-founded
<-is-extensional : is-extensional _<_
<-is-extensional zero zero f g = refl
<-is-extensional zero (succ n) f g = unique-from-𝟘 (g zero (zero-least n))
<-is-extensional (succ m) (zero) f g = unique-from-𝟘 (f zero (zero-least m))
<-is-extensional (succ m) (succ n) f g = ap succ (≤-anti m n γ₁ γ₂)
where
γ₁ : m ≤ℕ n
γ₁ = f m (≤-refl m)
γ₂ : n ≤ℕ m
γ₂ = g n (≤-refl n)
ℕ-ordinal : is-well-order _<_
ℕ-ordinal = <-is-prop-valued , <-is-well-founded , <-is-extensional , <-trans
\end{code}
Induction on z, then x, then y:
\begin{code}
ℕ-cotransitive : cotransitive _<_
ℕ-cotransitive zero y zero l = inr l
ℕ-cotransitive (succ x) y zero l = inr (≤-trans 1 (succ(succ x)) y ⋆ l)
ℕ-cotransitive zero (succ y) (succ z) l = inl (zero-least y)
ℕ-cotransitive (succ x) (succ y) (succ z) l = γ IH
where
IH : (x < z) + (z < y)
IH = ℕ-cotransitive x y z l
γ : (x < z) + (z < y) → (succ x < succ z) + (succ z < succ y)
γ (inl l) = inl (succ-monotone (succ x) z l)
γ (inr r) = inr (succ-monotone (succ z) y r)
\end{code}
Added December 2019.
\begin{code}
open import NotionsOfDecidability.Decidable
open import NotionsOfDecidability.Complemented
≤-decidable : (m n : ℕ ) → is-decidable (m ≤ n)
≤-decidable zero n = inl (zero-least n)
≤-decidable (succ m) zero = inr (zero-least' m)
≤-decidable (succ m) (succ n) = ≤-decidable m n
<-decidable : (m n : ℕ ) → is-decidable (m < n)
<-decidable m n = ≤-decidable (succ m) n
\end{code}
Bounded minimization (added 14th December 2019):
\begin{code}
βμ : (A : ℕ → 𝓤 ̇ )
→ is-complemented A
→ (k : ℕ)
→ (Σ m ꞉ ℕ , (m < k) × A m × ((n : ℕ) → A n → m ≤ n))
+ ((n : ℕ) → A n → n ≥ k)
βμ A δ 0 = inr (λ n a → zero-least n)
βμ A δ (succ k) = γ
where
conclusion = (Σ m ꞉ ℕ , (m < succ k) × A m × ((n : ℕ) → A n → m ≤ n))
+ ((n : ℕ) → A n → n ≥ succ k)
f : (Σ m ꞉ ℕ , (m < k) × A m × ((n : ℕ) → A n → m ≤ n)) → conclusion
f (m , l , a , φ) = inl (m , <-trans m k (succ k) l (<-succ k) , a , φ)
g : ((n : ℕ) → A n → k ≤ n) → conclusion
g φ = cases g₀ g₁ (δ k)
where
g₀ : A k → conclusion
g₀ a = inl (k , ≤-refl k , a , φ)
g₁ : ¬ A k → conclusion
g₁ u = inr ψ
where
ψ : (n : ℕ) → A n → succ k ≤ n
ψ 0 a = 𝟘-elim (v a)
where
p : k = 0
p = zero-least'' k (φ 0 a)
v : ¬ A 0
v = transport (λ - → ¬ A -) p u
ψ (succ n) a = III
where
I : k ≤ succ n
I = φ (succ n) a
II : k ≠ succ n
II p = transport (λ - → ¬ A -) p u a
III : k ≤ n
III = ≤-down k n I II
γ : conclusion
γ = cases f g (βμ A δ k)
\end{code}
Given k : ℕ with A k, find the least m : ℕ with A m, by reduction to
bounded minimization:
\begin{code}
Σμ : (ℕ → 𝓤 ̇ ) → 𝓤 ̇
Σμ A = Σ m ꞉ ℕ , A m × ((n : ℕ) → A n → m ≤ n)
least-from-given : (A : ℕ → 𝓤 ̇ ) → is-complemented A → Σ A → Σμ A
least-from-given A δ (k , a) = γ
where
f : (Σ m ꞉ ℕ , (m < k) × A m × ((n : ℕ) → A n → m ≤ n)) → Σμ A
f (m , l , a' , φ) = m , a' , φ
g : ((n : ℕ) → A n → k ≤ n) → Σμ A
g φ = k , a , φ
γ : Σμ A
γ = cases f g (βμ A δ k)
\end{code}
20th November 2020.
\begin{code}
open import Naturals.Addition renaming (_+_ to _∔_)
max : ℕ → ℕ → ℕ
max zero n = n
max (succ m) zero = succ m
max (succ m) (succ n) = succ (max m n)
max-idemp : (x : ℕ) → max x x = x
max-idemp zero = refl
max-idemp (succ x) = ap succ (max-idemp x)
max-comm : (m n : ℕ) → max m n = max n m
max-comm zero zero = refl
max-comm zero (succ n) = refl
max-comm (succ m) zero = refl
max-comm (succ m) (succ n) = ap succ (max-comm m n)
max-assoc : (x y z : ℕ) → max (max x y) z = max x (max y z)
max-assoc zero y z = refl
max-assoc (succ x) zero z = refl
max-assoc (succ x) (succ y) zero = refl
max-assoc (succ x) (succ y) (succ z) = ap succ (max-assoc x y z)
max-ord→ : (x y : ℕ) → x ≤ y → max x y = y
max-ord→ zero y le = refl
max-ord→ (succ x) zero le = 𝟘-elim le
max-ord→ (succ x) (succ y) le = ap succ (max-ord→ x y le)
max-ord← : (x y : ℕ) → max x y = y → x ≤ y
max-ord← zero y p = ⋆
max-ord← (succ x) zero p = 𝟘-elim (positive-not-zero x p)
max-ord← (succ x) (succ y) p = max-ord← x y (succ-lc p)
max-≤-upper-bound : (m n : ℕ) → m ≤ max m n
max-≤-upper-bound zero n = ⋆
max-≤-upper-bound (succ m) zero = ≤-refl m
max-≤-upper-bound (succ m) (succ n) = max-≤-upper-bound m n
max-≤-upper-bound' : (m n : ℕ) → m ≤ max n m
max-≤-upper-bound' zero n = ⋆
max-≤-upper-bound' (succ m) zero = ≤-refl m
max-≤-upper-bound' (succ m) (succ n) = max-≤-upper-bound' m n
minus : (m n : ℕ) → n ≤ m → ℕ
minus zero n le = zero
minus (succ m) zero ⋆ = succ m
minus (succ m) (succ n) le = minus m n le
minus-property : (m n : ℕ) (le : n ≤ m) → minus m n le ∔ n = m
minus-property zero zero ⋆ = refl
minus-property (succ m) zero ⋆ = refl
minus-property (succ m) (succ n) le = ap succ (minus-property m n le)
max-minus-property : (m n : ℕ)
→ minus (max m n) m (max-≤-upper-bound m n) ∔ m = max m n
max-minus-property m n = minus-property (max m n) m (max-≤-upper-bound m n)
\end{code}
Tom de Jong, 5 November 2021.
\begin{code}
<-trichotomous : (n m : ℕ) → (n < m) + (n = m) + (m < n)
<-trichotomous zero zero = inr (inl refl)
<-trichotomous zero (succ m) = inl ⋆
<-trichotomous (succ n) zero = inr (inr ⋆)
<-trichotomous (succ n) (succ m) = γ IH
where
γ : (n < m) + (n = m) + (m < n)
→ (succ n < succ m) + (succ n = succ m) + (succ m < succ n)
γ (inl k) = inl k
γ (inr (inl e)) = inr (inl (ap succ e))
γ (inr (inr l)) = inr (inr l)
IH : (n < m) + (n = m) + (m < n)
IH = <-trichotomous n m
\end{code}
Added 12/05/2020 by Andrew Sneap.
Following are proofs of common properties of strict and non-strict order of
Natural Numbers.
\begin{code}
≤-trans₂ : (x y u v : ℕ) → x ≤ y → y ≤ u → u ≤ v → x ≤ v
≤-trans₂ x y u v l₁ l₂ = ≤-trans x u v I
where
I : x ≤ u
I = ≤-trans x y u l₁ l₂
<-trans₂ : (x y u v : ℕ) → x < y → y < u → u < v → x < v
<-trans₂ x y u v l₁ l₂ = <-trans x u v I
where
I : x < u
I = <-trans x y u l₁ l₂
≤-<-trans : (x y z : ℕ) → x ≤ y → y < z → x < z
≤-<-trans x y z l₁ l₂ = ≤-trans (succ x) (succ y) z l₁ l₂
<-≤-trans : (x y z : ℕ) → x < y → y ≤ z → x < z
<-≤-trans x y z l₁ l₂ = ≤-trans (succ x) y z l₁ l₂
≤-n-monotone-right : (x y z : ℕ) → x ≤ y → (x +' z) ≤ (y +' z)
≤-n-monotone-right x y 0 l = l
≤-n-monotone-right x y (succ n) l = ≤-n-monotone-right x y n l
≤-n-monotone-left : (x y z : ℕ) → x ≤ y → (z +' x) ≤ (z +' y)
≤-n-monotone-left x y z l = transport₂ _≤_ γ₁ γ₂ γ₃
where
γ₁ : x ∔ z = z ∔ x
γ₁ = addition-commutativity x z
γ₂ : y ∔ z = z ∔ y
γ₂ = addition-commutativity y z
γ₃ : x ∔ z ≤ y ∔ z
γ₃ = ≤-n-monotone-right x y z l
≤-adding : (x y u v : ℕ) → x ≤ y → u ≤ v → (x +' u) ≤ (y +' v)
≤-adding x y u v l₁ l₂ = ≤-trans (x +' u) (y +' u) (y +' v) γ₁ γ₂
where
γ₁ : x ∔ u ≤ y ∔ u
γ₁ = ≤-n-monotone-right x y u l₁
γ₂ : y ∔ u ≤ y ∔ v
γ₂ = ≤-n-monotone-left u v y l₂
<-succ-monotone : (x y : ℕ) → x < y → succ x < succ y
<-succ-monotone x y = id
<-n-monotone-right : (x y z : ℕ) → x < y → (x +' z) < (y +' z)
<-n-monotone-right x y 0 l = l
<-n-monotone-right x y (succ z) l = <-n-monotone-right x y z l
<-n-monotone-left : (x y z : ℕ) → x < y → (z +' x) < (z +' y)
<-n-monotone-left x y z l = transport₂ _<_ γ₁ γ₂ γ₃
where
γ₁ : x ∔ z = z ∔ x
γ₁ = addition-commutativity x z
γ₂ : y ∔ z = z ∔ y
γ₂ = addition-commutativity y z
γ₃ : x ∔ z < y ∔ z
γ₃ = <-n-monotone-right x y z l
<-adding : (x y u v : ℕ) → x < y → u < v → (x +' u) < (y +' v)
<-adding x y u v l₁ l₂ = <-trans (x +' u) (y +' u) (y +' v) γ₁ γ₂
where
γ₁ : x ∔ u < y ∔ u
γ₁ = <-n-monotone-right x y u l₁
γ₂ : y ∔ u < y ∔ v
γ₂ = <-n-monotone-left u v y l₂
<-+ : (x y z : ℕ) → x < y → x < y +' z
<-+ x y z l₁ = ≤-trans (succ x) y (y +' z) l₁ l₂
where
l₂ : y ≤ y +' z
l₂ = ≤-+ y z
equal-gives-less-than-or-equal : (x y : ℕ) → x = y → x ≤ y
equal-gives-less-than-or-equal x y p = transport (_≤ y) (p ⁻¹) (≤-refl y)
less-than-not-equal : (x y : ℕ) → x < y → ¬ (x = y)
less-than-not-equal x y r p = less-not-bigger-or-equal x y r γ
where
γ : y ≤ℕ x
γ = equal-gives-less-than-or-equal y x (p ⁻¹)
less-than-one-is-zero : (x : ℕ) → x < 1 → x = 0
less-than-one-is-zero 0 l = refl
less-than-one-is-zero (succ x) l = 𝟘-elim l
not-less-or-equal-is-bigger : (x y : ℕ) → ¬ (x ≤ y) → y < x
not-less-or-equal-is-bigger 0 y l = l (zero-least y)
not-less-or-equal-is-bigger (succ x) 0 l = zero-least x
not-less-or-equal-is-bigger (succ x) (succ y) l
= not-less-or-equal-is-bigger x y l
≤-dichotomous : (x y : ℕ) → (x ≤ y) + (y ≤ x)
≤-dichotomous zero y = inl ⋆
≤-dichotomous (succ x) zero = inr ⋆
≤-dichotomous (succ x) (succ y) = ≤-dichotomous x y
≥-dichotomy : (x y : ℕ) → (x ≥ y) + (x ≤ y)
≥-dichotomy 0 y = inr (zero-least y)
≥-dichotomy (succ x) 0 = inl (zero-least (succ x))
≥-dichotomy (succ x) (succ y) = ≥-dichotomy x y
subtraction' : (x y : ℕ) → x < y → Σ z ꞉ ℕ , (z +' x = y)
subtraction' 0 0 l = 𝟘-induction l
subtraction' 0 (succ y) l = (succ y) , refl
subtraction' (succ x) (succ y) l = pr₁ IH , ap succ (pr₂ IH)
where
IH : Σ z ꞉ ℕ , z +' x = y
IH = subtraction' x y l
subtraction'' : (x y : ℕ) → x < y → Σ z ꞉ ℕ , (succ z +' x = y)
subtraction'' x 0 l = 𝟘-elim l
subtraction'' 0 (succ y) l = y , refl
subtraction'' (succ x) (succ y) l = pr₁ IH , ap succ (pr₂ IH)
where
IH : Σ z ꞉ ℕ , (succ z +' x = y)
IH = subtraction'' x y l
order-split : (x y : ℕ) → (x < y) + (x ≥ y)
order-split 0 0 = inr (zero-least 0)
order-split 0 (succ y) = inl (zero-least (succ y))
order-split (succ x) 0 = inr (zero-least (succ x))
order-split (succ x) (succ y) = order-split x y
least-element-unique : {A : ℕ → 𝓤 ̇}
→ (σ : is-complemented A)
→ ((α , αₚ) : Σ k ꞉ ℕ , A k × ((z : ℕ) → A z → k ≤ z))
→ ((β , βₚ) : Σ n ꞉ ℕ , A n × ((z : ℕ) → A z → n ≤ z))
→ α = β
least-element-unique σ (α , α₀ , α₁) (β , β₀ , β₁) = ≤-anti α β I II
where
I : α ≤ β
I = α₁ β β₀
II : β ≤ α
II = β₁ α α₀
least-element-unique' : {A : ℕ → 𝓤 ̇}
→ (σ : is-complemented A)
→ (x y : ℕ)
→ (δ : Σ A)
→ x = pr₁ (least-from-given A σ δ)
→ y = pr₁ (least-from-given A σ δ)
→ x = y
least-element-unique' σ x y δ e₁ e₂ = e₁ ∙ e₂ ⁻¹
\end{code}
The following section provides an algorithm for bounded maximisation
of decidable propositions on Natural numbers, similar to the algorithm
for bounded-minimisation above.
We want to prove the following:
Given a complemented predicate A on naturals numbers and strict upper bound k,
either there exists a maximal element m such that m < k , A m holds and
(∀ n , A n → n ≤ m), or our predicate only holds for n ≥ k.
Proof:
We proceed by induction on the upper bound. Given an upper bound of 0, we
are done, because there are no natural numbers less than 0.
Now we consider the induction hypothesis that our statement is true for an upper
bound k. We consider each case.
Case 1: We have some maximal element m such that A m holds, with m < k.
Since A is decidable, we find that either A k holds, or it doesn't. If it holds,
then have a new maximal element A k, with k < k + 1.
Case 2: The predicate does not hold for any m < k. Again, we inspect A k. If it
holds, then we have found a maximal (and the only) element m < k + 1. Otherwise,
the statement does not hold for any n is our range.
Also given are the types of maximal element m : ℕ such that A m holds, given an
upper bound k
\begin{code}
maximal-element : (A : ℕ → 𝓤 ̇) → (k : ℕ) → 𝓤 ̇
maximal-element A k
= Σ m ꞉ ℕ , (m < k × A m × ((n : ℕ) → n < k → A n → n ≤ m))
maximal-element' : (A : ℕ → 𝓤 ̇) → (k : ℕ) → 𝓤 ̇
maximal-element' A k
= Σ m ꞉ ℕ , (m ≤ k × A m × ((n : ℕ) → n ≤ k → A n → n ≤ m))
no-maximal-element : (A : ℕ → 𝓤 ̇) → (k : ℕ) → 𝓤 ̇
no-maximal-element A k = (n : ℕ) → A n → n ≥ k
no-maximal-element' : (A : ℕ → 𝓤 ̇) → (k : ℕ) → 𝓤 ̇
no-maximal-element' A k = (n : ℕ) → A n → k < n
bounded-maximisation : (A : ℕ → 𝓤 ̇)
→ is-complemented A
→ (k : ℕ)
→ maximal-element A k + no-maximal-element A k
bounded-maximisation A δ 0 = inr (λ n _ → zero-least n)
bounded-maximisation A δ (succ k) = γ (δ k) (bounded-maximisation A δ k)
where
γ : A k + ¬ A k
→ maximal-element A k + no-maximal-element A k
→ maximal-element A (succ k) + no-maximal-element A (succ k)
γ (inl Ak) (inl (m , l , Am , ψ)) = inl (k , <-succ k , Ak , ψ')
where
ψ' : (n : ℕ) → n < succ k → A n → n ≤ k
ψ' n l' An = l'
γ (inr ¬Ak) (inl (m , l , Am , ψ)) = inl (m , l' , Am , ψ')
where
l' : m < succ k
l' = <-trans m k (succ k) l (<-succ k)
ψ' : (n : ℕ) → n < succ k → A n → n < succ m
ψ' n l' An = ρ (<-split n k l')
where
ρ : (n < k) + (n = k) → n < succ m
ρ (inl l'') = ψ n l'' An
ρ (inr e) = 𝟘-elim (¬Ak (transport A e An))
γ (inl Ak) (inr ω) = inl (k , <-succ k , Ak , ψ)
where
ψ : (n : ℕ) → n < succ k → A n → n ≤ k
ψ n l An = l
γ (inr ¬Ak) (inr ψ) = inr ψ'
where
ψ' : (n : ℕ) → A n → n ≥ succ k
ψ' n An = ρ (<-split k n (ψ n An))
where
ρ : (k < n) + (k = n) → n ≥ succ k
ρ (inl l') = l'
ρ (inr e) = 𝟘-elim (¬Ak (transport A (e ⁻¹) An))
\end{code}
We can use the above result to prove the same statement for inclusive order.
\begin{code}
bounded-maximisation' : (A : ℕ → 𝓤 ̇)
→ is-complemented A
→ (k : ℕ)
→ maximal-element' A k + no-maximal-element' A k
bounded-maximisation' A δ k = bounded-maximisation A δ (succ k)
no-maximal-lemma : (A : ℕ → 𝓤 ̇)
→ (k : ℕ)
→ no-maximal-element A k
→ ¬ maximal-element A k
no-maximal-lemma A k ω (m , l , Am , ψ) = not-less-than-itself k β
where
α : k ≤ m
α = ω m Am
β : k < k
β = ≤-<-trans k m k α l
\end{code}
With above machinery in mind, we can now produce maximal elements of
propositions of Natural Numbers, given some initial Natural Number for
which the property holds. Of course, we must provide an upper bound.
\begin{code}
maximal-from-given : (A : ℕ → 𝓤 ̇)
→ (b : ℕ)
→ is-complemented A
→ Σ k ꞉ ℕ , A k × k < b
→ maximal-element A b
maximal-from-given A b δ (k , Ak , l) = Cases (bounded-maximisation A δ b) γ₁ γ₂
where
γ₁ : maximal-element A b → maximal-element A b
γ₁ = id
γ₂ : no-maximal-element A b → maximal-element A b
γ₂ ω = 𝟘-elim (not-less-than-itself b β)
where
α : b ≤ℕ k
α = ω k Ak
β : b < b
β = ≤-<-trans b k b α l
maximal-from-given' : (A : ℕ → 𝓤 ̇)
→ (b : ℕ)
→ is-complemented A
→ Σ k ꞉ ℕ , A k × k ≤ b
→ maximal-element' A b
maximal-from-given' A b = maximal-from-given A (succ b)
\end{code}
Multiplication preserves non-strict order, and this is proved by induction.
In the base case, it is required to prove that 0 ≤ 0 which is true by
definition. In the inductive case, we need to prove that
m * succ k ≤ n * succ k, or by definitional equality m + m * k ≤ n + n * k.
By the inductive hypothesis, m * k ≤ n * k, and we have that m ≤ n, so we
can use the result which says we can combine two order relations into one.
\begin{code}
open import Naturals.Multiplication
multiplication-preserves-order : (m n k : ℕ) → m ≤ n → m * k ≤ n * k
multiplication-preserves-order m n 0 l = zero-least 0
multiplication-preserves-order m n (succ k) l = γ
where
IH : m * k ≤ n * k
IH = multiplication-preserves-order m n k l
γ : m * (succ k) ≤ n * (succ k)
γ = ≤-adding m n (m * k) (n * k) l IH
\end{code}
For strict order, order is only preserved when multiplying by a value
greater than 0. Again by induction, the base case is trivial since we
are multiplying by 1. The inductive case is similar to the above
proof.
\begin{code}
multiplication-preserves-strict-order : (m n k : ℕ)
→ m < n
→ m * succ k < n * succ k
multiplication-preserves-strict-order m n 0 l = l
multiplication-preserves-strict-order m n (succ k) l = γ
where
IH : m * succ k < n * succ k
IH = multiplication-preserves-strict-order m n k l
γ : m * succ (succ k) < n * succ (succ k)
γ = <-adding m n (m * succ k) (n * succ k) l IH
\end{code}
If x * (y + 1) ≤ z, then x ≤ z. This is a useful property to have, and
proof follows from x ≤ x * y + 1 and transitivity of order.
A similar proof for strict order is sometimes useful.
\begin{code}
product-order-cancellable : (x y z : ℕ) → x * (succ y) ≤ z → x ≤ z
product-order-cancellable x 0 z = id
product-order-cancellable x (succ y) z l = γ
where
I : x ≤ x ∔ x * succ y
I = ≤-+ x (x * succ y)
γ : x ≤ z
γ = ≤-trans x (x * succ (succ y)) z I l
less-than-pos-mult : (x y z : ℕ) → x < y → x < y * succ z
less-than-pos-mult x y z l = <-+ x y (y * z) l
\end{code}
Lane Biocini, 07 September 2023
Here we define some order lemmas for the Absolute Difference operation
and then prove the analog of the triangle inequality for the Natural
Numbers under it.
\begin{code}
≤-diff : (x y : ℕ) → ∣ x - y ∣ ≤ x +' y
≤-diff x zero = ≤-refl x
≤-diff zero (succ y) = ≤-+' zero y
≤-diff (succ x) (succ y) = γ
where
Γ : (x +' y) ≤ℕ (succ x +' y)
Γ = ≤-trans (x +' y) (succ (x +' y)) (succ x +' y)
(≤-succ (x +' y))
(equal-gives-less-than-or-equal (succ (x +' y)) (succ x +' y)
(succ-left x y ⁻¹))
γ : ∣ x - y ∣ ≤ℕ succ (succ x +' y)
γ = ≤-trans₂ ∣ x - y ∣ (x +' y) (succ x +' y) (succ (succ x +' y))
(≤-diff x y) Γ (≤-succ (succ x +' y))
≤-diff-minus : (x y : ℕ) → x ≤ y +' ∣ y - x ∣
≤-diff-minus zero y = ⋆
≤-diff-minus (succ x) zero = ≤-+' zero x
≤-diff-minus (succ x) (succ y) = γ
where
Γ : x ≤ℕ (y +' ∣ y - x ∣)
Γ = ≤-diff-minus x y
γ : succ x ≤ℕ (succ y +' ∣ y - x ∣)
γ = ≤-trans (succ x) (succ (y +' ∣ y - x ∣)) (succ y +' ∣ y - x ∣)
(succ-monotone x (y +' ∣ y - x ∣) Γ)
(equal-gives-less-than-or-equal
(succ (y +' ∣ y - x ∣)) (succ y +' ∣ y - x ∣)
(succ-left y ∣ y - x ∣ ⁻¹))
≤-diff-plus : (x y : ℕ) → x ≤ℕ (∣ x - y ∣ +' y)
≤-diff-plus zero y = ⋆
≤-diff-plus (succ x) zero = ≤-refl x
≤-diff-plus (succ x) (succ y) = ≤-diff-plus x y
triangle-inequality : (x y z : ℕ) → ∣ x - z ∣ ≤ ∣ x - y ∣ +' ∣ y - z ∣
triangle-inequality zero y z =
≤-trans₂ ∣ zero - z ∣ z (y +' ∣ y - z ∣) (∣ zero - y ∣ +' ∣ y - z ∣) Γ α γ
where
Γ : ∣ zero - z ∣ ≤ℕ z
Γ = equal-gives-less-than-or-equal ∣ zero - z ∣ z (minus-nothing z)
α : z ≤ℕ (y +' ∣ y - z ∣)
α = ≤-diff-minus z y
β : y ≤ℕ ∣ zero - y ∣
β = equal-gives-less-than-or-equal y ∣ zero - y ∣ (minus-nothing y ⁻¹)
γ : (y +' ∣ y - z ∣) ≤ℕ (∣ zero - y ∣ +' ∣ y - z ∣)
γ = ≤-adding y ∣ zero - y ∣ ∣ y - z ∣ ∣ y - z ∣ β (≤-refl ∣ y - z ∣)
triangle-inequality (succ x) zero zero = ≤-refl x
triangle-inequality (succ x) zero (succ z) =
≤-trans₂ ∣ x - z ∣ (x +' z) (succ (x +' z)) (succ (succ x +' z))
(≤-diff x z)
(≤-succ (x +' z))
(≤-trans (x +' z) (succ (x +' z)) (succ x +' z) (≤-succ (x +' z)) α )
where
α : succ (x +' z) ≤ℕ (succ x +' z)
α = equal-gives-less-than-or-equal (succ (x +' z)) (succ x +' z)
(succ-left x z ⁻¹)
triangle-inequality (succ x) (succ y) zero = ≤-diff-plus x y
triangle-inequality (succ x) (succ y) (succ z) = triangle-inequality x y z
\end{code}